Scutellarin-induced A549 cell apoptosis depends on activation of the transforming growth factor-β1/smad2/ROS/caspase-3 pathway - Zhang Guang-Yan (De Gruyter, 2021)
Scutellarin plays an anti-tumor role in A549 lung cancer cells, but the underlying mechanism is unclear. In this study, scutellarin was used to treat A549 cells for 12, 24, and 48 h, followed by the addition of Tempo, a selective scavenger of mitochondrial reactive oxygen species (ROS) and SB431542, a transforming growth factor (TGF)-β1 receptor inhibitor. A dihydroethidium fluorescence probe was used to measure the intracellular ROS level, Cell Counting Kit-8 (CCK-8) was used to detect cell viability, and flow cytometry was performed to examine apoptosis. Western blots were used to detect the total protein level of TGF-β1, p-smad2, and cleaved caspase-3 in A549 cells. The results showed that scutellarin significantly inhibited cell viability and increased apoptosis. Scutellarin also promoted intracellular ROS production, TGF-β1/smad2 signaling pathway activation, and cleaved caspase-3 expression, which was partly reversed by Tempo. Moreover, scutellarin-induced intracellular ROS production and cleaved caspase-3 expression were inhibited by blocking the TGF-β1/smad2 pathway with SB431542. In conclusion, scutellarin promoted apoptosis and intracellular ROS accumulation, which could be abrogated by Tempo and SB431542 treatment in A549 cells. Our study indicated that scutellarin induced A549 cell apoptosis via the TGF-β1/smad2/ROS/caspase-3 pathway.